Design and build an AED information gathering mobile application - Tan, Michelle Wan Shan (2017)
An Automated External Defibrillator (AED) is a vital device in saving the lives of people in the event of cardiac arrest [1]. However, there is currently only one official mobile application in Singapore to source out AEDs in the vicinity. In collaboration with the Singapore Civil Defence Force (SCDF), this project aims to create an android mobile application using Android Studio that serves as a platform for getting the general population to help update the current database with more AEDs’ locations and associated information. It uses a crowdsourcing approach where the application offers an interface for the public to contribute location-based content pertaining to the locations of the AEDs. Some gamification features are to be included as well to encourage more users to actively seek out AEDs.